Does immediate hormone replacement therapy affect the oncologic outcome in endometrial cancer survivors?. Issue 2 (1st March 2006) - Ayhan, A.; Taskiran, C.; Simsek, S.; Sever, Atike
Abstract : The purpose of this study was to evaluate the effect of immediate hormone replacement therapy (HRT) on oncologic outcome of patients with endometrial cancer. The patients were recruited prospectively after extensive discussion of risks and benefits of HRT. Continuous daily regimen of 0.625 mg conjugated equine estrogen plus 2.5 mg medroxyprogesterone acetate was initiated 4–8 weeks after surgery at first postoperative visit. The patients who had the same characteristics with the HRT group were assigned as a control group. Overall, 50 patients received HRT. There was no significant difference with respect to prognosticators between the HRT users and the control group. Seven patients (14%) stopped the use of HRT. Only two patients stopped the therapy before 24 months, and all the remaining patients used HRT for at least 24 months, with a mean value of 49.1 months. Neither the patients who used HRT nor the ones who left the therapy had recurrence at the time of writing of this article. This prospective case–control study showed that immediate postoperative use of HRT did not increase the recurrence or death rates in endometrial cancer survivors.